Computed tomography derived fractional flow reserve testing in stable patients with typical angina pectoris: influence on downstream rate of invasive coronary angiography. (20th April 2017) - Jensen, Jesper Møller; Bøtker, Hans Erik; Mathiassen, Ole Norling; Grove, Erik Lerkevang; Øvrehus, Kristian Altern; Pedersen, Kamilla Bech; Terkelsen, Christian Juhl; Christiansen, Evald Høj; Maeng, Michael; Leipsic, Jonathon; Kaltoft, Anne; Jakobsen, Lars; et al.
Abstract: Aims: To assess the use of downstream coronary angiography (ICA) and short-term safety of frontline coronary CT angiography (CTA) with selective CT-derived fractional flow reserve (FFRCT ) testing in stable patients with typical angina pectoris. Methods and results: Between 1 January 2016 and 30 June 2016 all patients ( N = 774) referred to non-emergent ICA or coronary CTA at Aarhus University Hospital on a suspicion of CAD had frontline CTA performed. Downstream testing and treatment within 3 months and adverse events ≥90 days were registered. Patients were divided into two groups according to the presence of typical angina pectoris, which according to local practice would have resulted in referral to ICA, (low-intermediate-risk, n = 593 [76%]; high-risk, n = 181 [24%]) with mean pre-test probability of CAD of 31 ± 16% and 67 ± 16%, respectively. Coronary CTA was performed in 745 (96%) patients in whom FFRCT was prescribed in 212 (28%) patients. In the high- vs. low-intermediate-risk group, ICA was cancelled in 75% vs. 91%. Coronary revascularization was performed more frequently in high-risk than in low-intermediate-risk patients, 76% vs. 52% ( P = 0.03). Mean follow-up time was 157 ± 50 days. Serious clinical events occurred in four patients, but not in any patients with cancelled ICA by coronary CTA with selective FFRCT testing. Conclusion: Frontline coronary CTA with selective FFRCT testing in stable patients with typical angina pectoris in real-world practice is associated with a high rate of safe cancellation of planned ICAs.